Effects of Dietary Macleaya cordata Extract on Growth Performance, Biochemical Indices, and Intestinal Microbiota of Yellow-Feathered Broilers Subjected to Chronic Heat Stress - Mingcan Wang; Junkai Zhang; Xiuqiong Huang; Yisong Liu; Jianguo Zeng (Animals, 2022)
This study investigated the effect of dietary Macleaya cordata extract (MCE) supplementation on the growth performance, serum parameters, and intestinal microbiota of yellow-feather broilers under heat stress. A total of 216 yellow-feather broilers (28-days-old) were randomly allotted into three groups. A control group (CON) (24 ± 2 °C) and heat stress group (HS) (35 ± 2 °C) received a basal diet, and heat-stressed plus MCE groups (HS-MCE) (35 ± 2 °C) were fed the basal diet with 1000 mg/kg MCE for 14 consecutive days. The results revealed that MCE supplementation improved the final body weight, average daily feed intake, average daily gain, and spleen index when compared with the HS group (p < 0.05). In addition, MCE supplementation decreased (p < 0.05) the activities of aspartate aminotransferase, alanine aminotransferase, lactate dehydrogenase, and creatinine, and increased (p < 0.05) the glucose level and alkaline phosphatase activity in heat-stressed yellow-feathered broilers. Moreover, MCE treatment alleviated heat-stress-induced intestinal flora disturbances, decreased the Bacteroidota and Bacteroides relative abundances, and increased Firmicutes. A linear discriminant analysis effect size analysis found five differentially abundant taxa in the HS-MCE group, including Alistipes, Rikenellaceae, Mogibacterium, Butyrivibrio, and Lachnospira. These results suggest that MCE can alleviate HS-induced decline in growth performance by modulating blood biochemical markers and cecal flora composition in broilers.